ESGO/ISUOG/IOTA/ESGE Consensus Statement on preoperative diagnosis of ovarian tumors. (10th June 2021) - Timmerman, D.; Planchamp, F.; Bourne, T.; Landolfo, C.; du Bois, A.; Chiva, L.; Cibula, D.; Concin, N.; Fischerova, D.; Froyman, W.; Gallardo, G.; Lemley, B.; et al.
ABSTRACT: The European Society of Gynaecological Oncology (ESGO), the International Society of Ultrasound in Obstetrics and Gynecology (ISUOG), the International Ovarian Tumour Analysis (IOTA) group and the European Society for Gynaecological Endoscopy (ESGE) jointly developed clinically relevant and evidence‐based statements on the preoperative diagnosis of ovarian tumors, including imaging techniques, biomarkers and prediction models . ESGO/ISUOG/IOTA/ESGE nominated a multidisciplinary international group, including expert practising clinicians and researchers who have demonstrated leadership and expertise in the preoperative diagnosis of ovarian tumors and management of patients with ovarian cancer (19 experts across Europe). A patient representative was also included in the group. To ensure that the statements were evidence‐based, the current literature was reviewed and critically appraised . Preliminary statements were drafted based on the review of the relevant literature. During a conference call, the whole group discussed each preliminary statement and a first round of voting was carried out. Statements were removed when consensus among group members was not obtained. The voters had the opportunity to provide comments/suggestions with their votes. The statements were then revised accordingly. Another round of voting was carried out according to the same rules to allow the whole group to evaluate the revised version of the statements. The group achieved consensus on 18 statements . This Consensus Statement presents these ESGO/ISUOG/IOTA/ESGE statements on the preoperative diagnosis of ovarian tumors and the assessment of carcinomatosis, together with a summary of the evidence supporting each statement . Abstract : This article's abstract has been translated into Spanish and Chinese. Follow the links from the abstract to view the translations. RESUMEN: Declaración de consenso de ESGO/ISUOG/IOTA/ESGE sobre el diagnóstico preoperatorio de los tumores de ovario La Sociedad Europea de Oncología Ginecológica (ESGO), la Sociedad Internacional de Ecografía en Obstetricia y Ginecología (ISUOG), el Grupo Internacional de Análisis de Tumores de Ovario (IOTA) y la Sociedad Europea de Endoscopia Ginecológica (ESGE) elaboraron conjuntamente declaraciones de importancia para la práctica clínica y con base empírica sobre el diagnóstico preoperatorio de los tumores de ovario, a partir de imágenes, biomarcadores y modelos de predicción, entre otras técnicas. La ESGO/ISUOG/IOTA/ESGE designó a un grupo internacional multidisciplinar, que incluye a personas expertas de la práctica clínica y la investigación que han demostrado liderazgo y experiencia en el diagnóstico preoperatorio de los tumores de ovario y en el tratamiento de las pacientes con cáncer de ovario (19 personas expertas de toda Europa). También se incluyó en el grupo a una representante de las pacientes. Para garantizar que las declaraciones tenían una base empírica, se revisó la literatura actual y se valoró de forma crítica. Se redactaron declaraciones preliminares basadas en la revisión de la literatura pertinente. La totalidad del grupo debatió durante una teleconferencia cada declaración preliminar y se llevó a cabo una primera ronda de votaciones. Las declaraciones se eliminaron cuando no se obtuvo el consenso entre los miembros del grupo. Los votantes tuvieron la oportunidad de aportar comentarios/sugerencias a la par que sus votos. Las declaraciones se revisaron en consecuencia. Se llevó a cabo otra ronda de votaciones según las mismas reglas para que todo el grupo pudiera evaluar la versión revisada de las declaraciones. El grupo logró un consenso sobre 18 declaraciones. Esta Declaración de Consenso presenta estas declaraciones de la ESGO/ISUOG/IOTA/ESGE sobre el diagnóstico preoperatorio de los tumores de ovario y la evaluación de la carcinomatosis, junto con un resumen de la evidencia que apoya cada declaración. 摘要: ESGO/ISUOG/IOTA/ESGE对卵巢肿瘤术前诊断的共识陈述 欧洲妇科肿瘤学会(ESGO)、国际妇产科超声学会(ISUOG)、国际卵巢肿瘤分析小组(IOTA)及欧洲妇科内窥镜学会(ESGE)，针对卵巢肿瘤术前诊断联合开发了临床相关的循证陈述，包括影像技术、生物指标和预测模型。 ESGO/ISUOG/IOTA/ESGE任命了一个国际多学科综合治疗团队，由专家执业临床医生和科研人员组成，这些成员(来自欧洲的19位专家)均具备领导力、卵巢肿瘤术前诊断的专业知识和管理卵巢肿瘤患者的经验。该小组中还包含了一位患者代表。为确保陈述以证据为基础，当前文献已得到评审和批评性评估。 初步陈述是以相关文献的评审为基础来起草的。在一次电话会议中，整个小组讨论了每条初步陈述并展开了第一轮投票。当共识在小组成员之中难以达成时，所涉及的陈述将被删除。投票人有机会就其投票提供评论或建议。每条陈述再得到相应的修改。另一轮投票又以相同的规则展开，让整个小组来评估陈述的修订版本。小组对18条陈述达成一致意见。 本共识陈述展示了ESGO/ISUOG/IOTA/ESGE针对卵巢肿瘤术前诊断的报告、癌症扩散的评估，以及对每条陈述都有支持性证据的总结。